Optimizing a Hematology/Oncology Curriculum for Internal Medicine Residents: A Two-Institution Modified Delphi Study - Jordyn F. Silverstein; Laura A. Huppert; Matthew Schwede; Sarah Goglin; Tyler P. Johnson; Jennifer M. Babik; Sam Brondfield (Journal of Cancer Education, 2026)
Purpose. Although hematology/oncology (H/O) topics are essential for clinicians, many internal medicine (IM) residents perceive inadequate H/O education. This perception may be due to the lack of a standardized H/O curriculum. To address this gap, we aimed to achieve consensus about the most important H/O topics for IM residents to learn. Methods. In 2023, we conducted a 2-round modified Delphi study of IM generalists and H/O specialists at the University of California, San Francisco and Stanford University. In round 1, participants rated the importance of H/O topics on a 5-point scale (1 = very unimportant; 5 = very important). In round 2, participants viewed their own ratings vs. the group mean and could change their ratings. We used a content validity index (CVI, the percentage of respondents who rated the topic ≥ 4) of ≥ 75% to identify the most important topics. We calculated the effect sizes of between-group rating differences using Cohen’s d. Results. The round 1 and 2 response rates were 70% (92/132) and 77% (71/92), respectively. Ninety-one of the 239 topics met the CVI threshold (41 classical hematology, 14 malignant hematology, and 36 solid oncology), of which only 4 out of 91 (4%) had a large effect size, indicating agreement between generalists and specialists. There were 14 topics with a CVI of 100%, including deep venous thrombosis/pulmonary embolism, iron deficiency anemia, advance care planning, and management of end-of-life issues. Conclusion. With input from IM generalists and H/O specialists, we identified the most important H/O topics for IM residents, which can guide curriculum development.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Capturing expert uncertainty: ICC-informed soft labelling for volcano-seismicity - Sam Mitchinson; Jessica H. Johnson; Ben Milner; Oliver Lamb; Yannik Behr (Bulletin of Volcanology, 2025)
Reliable classification of volcano-seismic signals underpins monitoring and eruption forecasting and is an essential tool for advancing understanding of subsurface processes. However, traditional approaches may overlook the inherent uncertainty and variability between expert judgments. We introduce an innovative method that explicitly quantifies inter-expert agreement using the intraclass correlation coefficient (ICC) and incorporates this measure into probabilistic, ICC-informed soft labels, which can be fed into machine learning pipelines. We conducted a global survey involving 89 experts who classified a set of 80 volcano-seismic events from Ruapehu, New Zealand, providing continuous ratings for standard categories: volcano tectonic (VT), hybrid (HYB), long-period (LP), and other (OT). ICC agreement scores revealed that single-rater scores produce poor agreement between experts even for well-established VT and LP classifications. However, reliability significantly improved for these classifications when multiple expert ratings were combined, although, for HYB and OT categories, expert disagreement remained substantial. We developed a soft labelling methodology that weights class probabilities by their respective ICC scores, resulting in a distribution that naturally reflects expert uncertainty. This demonstrates that ICC-informed soft labels could provide a robust alternative to the hard label standard by explicitly capturing classification uncertainty and variability. Our fully probabilistic view has the potential to significantly enhance machine learning model accuracy, robustness, and transferability across volcanic systems and should provide a fundamental shift in how volcano-seismic data are labelled and interpreted within automated monitoring frameworks.

The influence of mycorrhizal hyphal connections and neighbouring plants on Plantago lanceolata physiology and nutrient uptake - Henry W. G. Birt; Lewis P. Allen; Sam Madge; Clare H. Robinson; Richard D. Bardgett; David Johnson (Mycorrhiza, 2025)
Most plants extend their zone of interaction with surrounding soils and plants via mycorrhizal hyphae, which in some cases can form common mycorrhizal networks with hyphal continuity to other neighbouring plants. These interactions can impact plant health and ecosystem function, yet the role of these radial plants in mycorrhizal interactions and subsequent plant performance remains underexplored. Here we investigated the influence of hyphal exploration and interaction with neighbouring mycorrhizal plants, plants that are weakly mycorrhizal, and a lack of neighbouring plants on the performance of Plantago lanceolata , a mycotrophic perennial herb common to many European grasslands, using mesh cores and the manipulation of neighbouring plant communities. Allowing growth of hyphae beyond the mesh core increased carbon capture above-ground and release below-ground as root exudates and resulted in the greater accumulation of elements relevant to plant health in P. lanceolata . However, contrary to expectations, the presence of mycorrhizal, or weakly mycorrhizal neighbours as well as an absence of neighbours did not significantly alter the benefits of hyphal networks to P. lanceolata . Our findings demonstrate that enabling the development of a fungal network beyond the immediate host rhizosphere significantly influences plant leaf elemental stoichiometry, enhances plant carbon capture, and increases the amount of carbon they release via their roots as exudates. Our experimental design also provides a simple set of controls to prevent attributing positive mycorrhizal effects to neighbouring plant connections.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Emissions from heavy-duty diesel, natural gas, and diesel-hybrid electric vehicles – Part 1. NOx, N2O and NH3 emissions - Hanwei Zhu; Chengguo Li; Cavan McCaffery; Sam Cao; Kent C. Johnson; Georgios Karavalakis; Thomas Durbin (Fuel, 2024)

Real-world particulate, GHG, and gaseous toxic emissions from heavy-duty diesel and natural gas vehicles - Zisimos Toumasatos; Hanwei Zhu; Thomas D. Durbin; Kent C. Johnson; Sam Cao; Georgios Karavalakis (Atmospheric Environment, 2024)

A comparative study of accuracy in major adaptive filters for motion artifact removal in sleep apnea tests - Yongrui Chen; Yurui Zheng; Sam Johnson; Richard Wiffen; Bin Yang (Medical & Biological Engineering & Computing, 2024)
Sleep apnea is probably the most common respiratory disorder; respiration and blood oxygen saturation (SpO 2 ) are major concerns in sleep apnea and are also the two main parameters checked by polysomnography (PSG, the gold standard for diagnosing sleep apnea). In this study, we used a simple, non-invasive monitoring system based on photoplethysmography (PPG) to continuously monitor SpO 2 and heart rate (HR) for individuals at home. Various breathing experiments were conducted to investigate the relationship between SpO 2 , HR, and apnea under different conditions, where two techniques (empirical formula and customized formula) for calculating SpO 2 and two methods (resting HR and instantaneous HR) for assessing HR were compared. Various adaptive filters were implemented to compare the effectiveness in removing motion artifacts (MAs) during the tests. This study fills the gap in the literature by comparing the performance of different adaptive filters on estimating SpO 2 and HR during apnea. The results showed that up-down finger motion introduced more MA than left-right motion, and the errors in SpO 2 estimation were increased as the frequency of movement was increased; due to the low sampling frequency features of these tests, the insertion of adaptive filter increased the noise in the data instead of eliminating the MA for SpO 2 estimation; the normal least mean squares (NLMS) filter is more effective in removing MA in HR estimation than other filters. Graphical abstract

On-road NOx and NH3 emissions measurements from in-use heavy-duty diesel and natural gas trucks in the South Coast air Basin of California - Hanwei Zhu; Tianyi Ma; Zisimos Toumasatos; Sam Cao; Georgios Karavalakis; Kent C. Johnson; Thomas Durbin (Atmospheric Environment, 2024)

Observations of the chemistry and concentrations of reactive Hg at locations with different ambient air chemistry - Mae Sexauer Gustin; Sarrah M. Dunham-Cheatham; Natalie Allen; Nicole Choma; William Johnson; Sam Lopez; Armistead Russell; Eric Mei; Olivier Magand; Aurélien Dommergue; Tyler Elgiar (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The ethics of intervening in animal behaviour for conservation - Thom van Dooren; Catherine J. Price; Peter B. Banks; Oded Berger-Tal; Matthew Chrulew; Jane Johnson; Gabrielle Lajeunesse; Kate E. Lynch; Clare McArthur; Finn C.G. Parker; Myles Oakey; Benjamin J. Pitcher; et al. (Trends in Ecology & Evolution, 2023)

Comparative analysis of UK net-zero scenarios: The role of energy demand reduction - Elliott Johnson; Sam Betts-Davies; John Barrett (Energy Policy, 2023)

Impact of sea ice transport on Beaufort Gyre liquid freshwater content - Sam B. Cornish; Morven Muilwijk; Jeffery R. Scott; Juliana M. Marson; Paul G. Myers; Wenhao Zhang; Qiang Wang; Yavor Kostov; Helen L. Johnson; John Marshall (Climate Dynamics, 2023)
The Arctic Ocean’s Beaufort Gyre (BG) is a wind-driven reservoir of relatively fresh seawater, situated beneath time-mean anticyclonic atmospheric circulation, and is covered by mobile pack ice for most of the year. Liquid freshwater accumulation in and expulsion from this gyre is of critical interest due to its potential to affect the Atlantic meridional overturning circulation and due to the importance of freshwater in modulating vertical fluxes of heat, nutrients and carbon in the ocean, and exchanges of heat and moisture with the atmosphere. Here, we investigate the hypothesis that wind-driven sea ice transport into/from the BG region influences the freshwater content of the gyre and its variability. To test this hypothesis, we use the results of a coordinated climate response function experiment with four ice-ocean models, in combination with targeted experiments using a regional setup of the MITgcm, in which we rotate the surface wind forcing vectors (thereby changing the ageostrophic component of these winds). Our results show that, via an effect on the net thermodynamic growth rate, anomalies in sea ice transport into the BG affect liquid freshwater adjustment. Specifically, increased ice import increases freshwater retention in the gyre, whereas ice export decreases freshwater in the gyre. Our results demonstrate that uncertainty in the ageostrophic component of surface winds, and in the dynamic sea ice response to these winds, has important implications for ice thermodynamics and freshwater. This sensitivity may explain some of the observed inter-model spread in simulations of Beaufort Gyre freshwater and its adjustment in response to wind forcing.

Biomechanics of nectar feeding explain flower orientation in plants pollinated by long-proboscid flies - Sam McCarren; Jeremy J. Midgley; Steven D. Johnson (The Science of Nature, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

“A shovel or a shopping cart”: lessons from ten years of disaster response by a student-led volunteer group - Sally Carlton; Sylvia Nissen; Jennifer H. K. Wong; Sam Johnson (Natural Hazards, 2022)

Genetic structure of a recent climate change-driven range extension - SAM C. BANKS; SCOTT D. LING; CRAIG R. JOHNSON; MAXINE P. PIGGOTT; JANE E. WILLIAMSON; LUCIANO B. BEHEREGARAY (Molecular Ecology, 2010)

WUA training and support in the Kyrgyz Republic - Sam H. Johnson; Joop Stoutjesdijk (Irrigation and Drainage, 2008)
After the collapse of the Soviet Union and the disbanding of state farms, on‐farm irrigation was in chaos. Many republics replaced their production brigades with water user associations (WUAs). In the Kyrgyz Republic, with World Bank support, the Department of Water Resources (DWR) established WUAs to take over on‐farm irrigation operation and maintenance (O&M). To ensure these were participatory, in 2002 the Republic passed a WUA Law. To date 451 WUAs have been legally registered under this law. As farmers had no experience with participatory associations, an intensive capacity development program was critical for success. Within the DWR WUA Support Units (SUs) at the central (1), provincial (7) and district (40) level were formed. International consultants and Central SU staff members provided more than 3000 days of training for staff members of SUs. In turn, SUs have provided more than 47 000 days of training for WUAs. Interactions with SUs and intensive training have strengthened WUA boards and encouraged member participation. Monitoring data documents increased the efficiency of water delivery, while fees paid by WUA members have increased annually in every province. WUAs have now formed 14 WUA federations responsible for off‐farm O&M. The success of these federations requires advanced capacity development for leaders and management staff. Copyright © 2008 John Wiley & Sons, Ltd.

Chromatin dynamics and the evolution of alternate promoter states - Gordon L. Hager; Cem Elbi; Thomas A. Johnson; Ty Voss; Akhilesh K. Nagaich; R. Louis Schiltz; Yi Qiu; Sam John (Chromosome Research, 2006)

Privatizing canal irrigation - Mark Svendsen; Fernando Gonzalez; Sam Johnson (Irrigation and Drainage, 2003)
Widespread dissatisfaction with state management of canal irrigation systems has focused intense interest on potential private sector remedies for the problems afflicting the sector. Privatization promises a number of benefits—lower operating costs, increased productivity, innovation, mobilization of capital, higher service quality, and larger service areas. However, canal irrigation is a natural monopoly, where the large capital investments required preclude multiple private service providers in a given service area. Nevertheless, the paper argues that there are a number of ways to take advantage of positive features of the private sector, without wasteful duplication of infrastructure or leaving farmers at the mercy of greedy investors. Three primary options—renewable management contracts, franchises, and self‐provision of services by clients—are described and illustrated. Another way to examine possibilities for privatization is to look at the types of organizations that provide irrigation services. The defining aspects of an organization are governance, source of funds, economic motive, and type of staff. The paper defines a set of five types of service providers based on these characteristics. These types are departments, authorities, districts, associations, and public utilities. The characteristics of each are discussed, with examples. To rise above the basic performance floor provided by a public bureaucracy, an institutional structure including private elements requires a supporting policy environment. Critical elements of a supportive environment include policy stability, legal respect for contracts and agreements, and reasonably impartial regulation, allocation, and adjudication. In the absence of a sufficiently supportive national governance environment, private elements in the irrigation management system are unlikely to flourish or, conversely, may have the ability to take advantage of weaker parties. Copyright © 2003 John Wiley & Sons, Ltd.

A case of segmental paternal isodisomy of chromosome 14 - Karen J. Coveler; Sam P. Yang; Reid V. Sutton; Jay M. Milstein; Yuan-Qing Wu; Cami Bois; Linda S. Beischel; John P. Johnson; Lisa G. Shaffer (Human Genetics, 2002)

Modeling the Pharmacokinetics and Pharmacodynamics of a Unique Oral Hypoglycemic Agent Using Neural Networks - Sam H. Haidar; Steven B. Johnson; Michael J. Fossler; Ajaz S. Hussain (Pharmaceutical Research, 2002)